Hubungan Antara Shyness dengan Kecemasan Komunikasi Interpersonal pada Mahasiswa Tahun Pertama Fakultas Psikologi Universitas Medan Area - Ribcha Nigia Nawuazitarry Duha; Sabrini Mentari Rezeki; Rina Mirza; Zefanya Natasya Jouma Manalu; Tania Rosani Simanjorang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the relationship between shyness and interpersonal communication anxiety among first-year students at the Faculty of Psychology, Universitas Medan Area. This research employed a quantitative approach with a correlational design using disproportionate stratified random sampling. A total of 167 students were selected from a population of 311. The instruments used were the Interpersonal Communication Anxiety Scale (65 items; reliability = 0.745) and the Shyness Scale (61 items; reliability = 0.741). Data were analyzed using Pearson’s Product Moment correlation. The results showed a significant positive relationship between shyness and interpersonal communication anxiety (r = 0.828, p < 0.05). This indicates that higher levels of shyness are associated with higher levels of interpersonal communication anxiety. Therefore, the hypothesis of this study was accepted.